Accumulation patterns of intracellular salts in a new halophilic amoeboflagellate, Euplaesiobystra salpumilio sp. nov., (Heterolobosea; Discoba) under hypersaline conditions - Lee, Hyeon Been; Jeong, Dong Hyuk; Park, Jong Soo (Frontiers in Microbiology, 2022)
Halophilic microbial eukaryotes are present in many eukaryotic lineages and major groups; however, our knowledge of their diversity is still limited. Furthermore, almost nothing is known about the intracellular accumulation of salts in most halophilic eukaryotes. Here, we isolate a novel halophilic microbial eukaryote from hypersaline water of 134 practical salinity units (PSU) in a solar saltern. This species is an amoeboflagellate (capable of the amoeba-flagellate-cyst transformation) in the heterolobosean group, and belongs to the genus Euplaesiobystra based on morphological data and 18S rDNA sequences. However, the isolate is distinct from any of the described Euplaesiobystra species. Especially, it is the smallest Euplaesiobystra to date, has a distinct cytostome, and grows optimally at 75–100 PSU. Furthermore, the phylogenetic tree of the 18S rDNA sequences demonstrates that the isolate forms a strongly supported group, sister to Euplaesiobystra hypersalinica. Thus, we propose that the isolate, Euplaesiobystra salpumilio, is a novel species. E. salpumilio displays a significantly increased influx of the intracellular Na+ and K+ at 50, 100, and 150 PSU, compared to freshwater species. However, the intracellular retention of the Na+ and K+ at 150 PSU does not significantly differ from 100 PSU, suggesting that E. salpumilio can extrude the Na+ and K+ from cells under high salinity conditions. Interestingly, actively growing E. salpumilio at 100 and 150 PSU may require more intracellular accumulation of Na+ than the no-growth but-viable state at 50 PSU. It seems that our isolate displays two salt metabolisms depending on the tested salinities. E. salpumilio shows a salt-in strategy for Na+ at lower salinity of 100 PSU, while it displays a salt-out strategy for Na+ at higher salinity of 150 PSU. Our results suggest that the novel halophilic E. salpumilio fundamentally uses a salt-out strategy at higher salinities, and the accumulation patterns of intracellular salts in this species are different from those in other halophilic microbial eukaryotes.